Efficacy and safety of pimavanserin in patients with Alzheimer's dementia psychosis in the HARMONY phase 3, randomized discontinuation study: a post hoc subgroup analysis. (20th December 2022) - Cummings, Jeffrey; Devanand, Davangere P; Ballard, Clive G; Tariot, Pierre N.; Hendrix, Suzanne B.; Dickson, Samuel P.; Li, Caiyan; Abler, Victor; Pathak, Sanjeev; Stankovic, Srdjan
Abstract: Background: Pimavanserin was investigated for the treatment of dementia‐related psychosis (DRP) in HARMONY (NCT03325556), a phase 3 randomized discontinuation study. As the study met the primary endpoint (one‐sided P = 0.0023), we evaluated the consistency of the efficacy for reducing the risk of relapse in the largest dementia patient subgroup (ie, Alzheimer's dementia psychosis [ADP] patients) treated with pimavanserin 34mg. Method: Enrolled DRP patients (N = 392) entered the 12‐week open‐label (OL) period and received pimavanserin 34mg daily. During weeks 1‐4, dose could be adjusted to 20mg at investigator discretion. Patients meeting prespecified response criteria at weeks 8 and 12 were randomized to continue pimavanserin or receive placebo for up to 26 weeks in the double‐blind (DB) period. The primary endpoint was time from randomization to adjudicated relapse. Efficacy analyses included patients at the interim analysis (IA); safety analyses included all dosed patients. Result: Of 260 ADP patients, 243 stayed on pimavanserin 34mg throughout the OL period; 17 patients received pimavanserin 20mg beyond OL week 4. At baseline, mean age in the pimavanserin 34mg group was 75.7 years; mean MMSE score was 16.0. Twenty‐nine patients were terminated with sponsor termination of the study; of the remaining 214 patients, 130 (60.7%) met response criteria at weeks 8 and 12 and were randomized. At the IA, 116 ADP patients were randomized to pimavanserin 34mg (N = 57) or placebo (N = 59). Hazard ratio for psychosis relapse risk with pimavanserin 34mg versus placebo was 0.466 (95% CI: 0.179, 1.214); 6/57 (10.5%) pimavanserin‐treated and 14/59 (23.7%) placebo‐treated patients met relapse criteria. Treatment‐emergent adverse events incidence rates were: OL, 29.6% (72/243); DB‐pimavanserin 34mg, 39.7% (25/63); DB‐placebo, 34.3% (23/67). Pimavanserin did not have a negative effect on Mini‐Mental State Examination or Extrapyramidal Symptom Rating Scale‐Abbreviated score change from baseline versus placebo in the DB period. Conclusion: In a study that met its primary endpoint, a post‐hoc subgroup analysis in ADP, although not statistically significant, demonstrated a clinically meaningful reduction in the risk of relapse was observed in patients treated with pimavanserin 34mg versus placebo. Pimavanserin was not associated with an adverse impact on cognition or motor function.